Analisis Usahatani Cabai Merah (Capsicum annum L.) pada Kelompok Tani Sumber Makmur Desa Sungai Ara Kecamatan Kempas Kabupaten Indragiri Hilir - Eko Pirmanto; Yeni Afiza; Yuslizar (Program Studi Agribisnis, Fakultas Pertanian, 2026)
This study aims to analyze the cost, income, and efficiency of red chili (Capsicum annum L.) farming managed by the Sumber Makmur Farmer Group in Sungai Ara Village, Kempas District, Indragiri Hilir Regency, Riau Province. The research employed a descriptive quantitative approach using survey methods. Data were collected through interviews with 20 farmers using structured questionnaires. The results showed that the average profit earned per planting season was IDR 54,208,850. The R/C ratio of 2.49 indicates that red chili farming in the study area is efficient and profitable. These findings suggest that red chili farming has strong potential as a source of income for farmers. This research is expected to serve as a reference for farmers and stakeholders in making decisions related to the development of horticultural agribusiness.